Dominant Coalitions Directing Acquisitions: Different Decision Makers, Different Decisions - Man Zhang, Cyndi; Greve, Henrich R. (Academy of Management Journal, 2019)
Coalitions are important in organizational decision making, but the question of how coalitions are built and make decisions in response to firm performance is still not sufficiently explored. In this study, we develop and test theory on how potential coalitions are built through shared experience and recruitment of allies. When organizations respond to performance relative to aspiration levels, either as problemistic search following low performance or opportunity exploration following high performance, members form coalitions to influence decisions. We develop theory of coalition formation that builds on upper echelons theory and the theory of dominant coalitions to predict how past experience of decision makers leads to preferred actions by each member and subsequent coalition formation. We use this theory to make new measures of potential coalitions and apply it to acquisitions made by firms in China. We find evidence that the experience of members of the key decision-making group—the board of directors—affects the potential coalition building, and hence the type of acquisition target, as predicted.